Intercropping Squash with Maize under Varying Planting System (Bangladesh Agronomy Journal, 2019)
The experiment was conducted at the research field of Agronomy Division, Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur during rabi seasons of 2014-15 and 2015-16 to find out the suitable planting arrangement of squash (var. Bulam House) with maize (var. BARI Hybrid maize-9) as intercropping for higher productivity and economic return. Seven treatment combinations viz. maize normal plating (75 cm Í 25 cm), maize normal plating (75 cm Í 25 cm) (100%) + 1 row squash (Plant to Plant 80 cm) (116%), maize paired row (37.5 cm Í 150 cm Í 37.5 cm) (100%) + 1 row squash (Plant to Plant 80 cm) (50%), maize paired row (100%) + 1 row squash (Plant to Plant 100 cm) (40%), maize paired row (100%) + 2 rows squash (Plant to Plant 80 cm) (100%), maize paired row (100%) + 2 rows squash (80%) (Plant to Plant 100 cm) and sole Squash (100 cm × 80 cm) were tested. Results showed that the highest grain yield of maize (9.47 t ha-1 in 2014-15 and 9.24 t ha-1 in 2015-16) and squash yield (28.19 t ha-1 in 2014-15 and 25.02 t ha-1 in 2015-16) were recorded in sole crop, respectively. Maximum mean maize equivalent yield (19.39 t ha-1) was recorded in maize paired row (100%) + 2 row squash (Plant to Plant 80 cm) (100%) combination in both the year. The highest gross return (Tk. 2,93,850 ha-1), gross margin (Tk. 1,92,450 ha-1) and BCR (2.95) were also obtained from the same combinations. Two years’ results revealed that maize paired row + 2 rows squash (Plant to Plant 80 cm) combination could be suitable for higher productivity and economic return.Bangladesh Agron. J. 2018, 21(2): 19-24